HUBUNGAN PERAN PEMIMPIN DENGAN PERKEMBANGAN TEKNOLOGI TELENURSING YANG MENJADI TREND ISSUE KEPERAWATAN DALAM MASA PANDEMI COVID-19 DI RUMAH SAKIT UMUM AL-FATAH AMBON - Dewi Arwini Bugis; Thalya Imanuel Sinay; Cosalina M Sangaji (Pasapua Health Journal, 2021)
Introduction: To improve the quality of telenursing services, a good leadership role is needed, so that in the implementation of telenursing that occurs in hospitals it can be well coordinated, including in serving the community when telenursing services are provided. What the leader does is understand his role as a leader in implementing telenursing so that subordinates or other workers can do it according to the procedure.The purpose of this research is to find out whether there is a relationship between the role of a leader and the development of telenursing information technology at Al-Fatah General Hospital in Ambon. Method: The research method used is descriptive with a cross sectional design. The research sample was taken using a total sampling technique with a total sample of 20 respondents. Bivariate analysis using fisher’s exact test.Results: The research results obtained were that some of the leaders at AlFatah Ambon General Hospital with good leadership roles were 13 respondents with good information technology developments as many as 6 respondents and information technology developments that were not good as many as 14 respondents. While respondents with a less good leader role were 7 respondents. There is no relationship between the role of the leader and the development of telenursing information technology with a p-valie of 0.007. Conclusion: This study shows that most of the leaders are not aware of the development of telenursing information technology.